Gre Factors Are Required for Biofilm Formation in Salmonella enterica Serovar Typhimurium by Targeting Transcription of the csgD Gene - Tania Gaviria-Cantin; Andrés Felipe Vargas; Youssef El Mouali; Carlos Jonay Jiménez; Annika Cimdins-Ahne; Cristina Madrid; Ute Römling; Carlos Balsalobre (Microorganisms, 2022)
Rdar biofilm formation of Salmonella typhimurium and Escherichia coli is a common ancient multicellular behavior relevant in cell–cell and inter-organism interactions equally, as in interaction with biotic and abiotic surfaces. With the expression of the characteristic extracellular matrix components amyloid curli fimbriae and the exopolysaccharide cellulose, the central hub for the delicate regulation of rdar morphotype expression is the orphan transcriptional regulator CsgD. Gre factors are ubiquitously interacting with RNA polymerase to selectively overcome transcriptional pausing. In this work, we found that GreA/GreB are required for expression of the csgD operon and consequently the rdar morphotype. The ability of the Gre factors to suppress transcriptional pausing and the 147 bp 5′-UTR of csgD are required for the stimulatory effect of the Gre factors on csgD expression. These novel mechanism(s) of regulation for the csgD operon might be relevant under specific stress conditions.